1992
DOI: 10.1073/pnas.89.22.11084
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanism by which stress accelerates growth of virally derived tumors.

Abstract: Stress accelerates the growth of certain types of tumors. Here we report a possible metabolic mechanism underlying this phenomenon. Some early features of transformation include increased number of glucose transporters and greatly enhanced rates of glucose uptake; this adaptation accommodates the vast energy demands needed for neoplastic growth. In contrast, glucocorticoids, a class of steroid hormones secreted during stress, inhibit glucose transport in various tissues; this is one route by which circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Tumour cells become resistant to the catabolic action of cortisol, which inhibits the uptake of glucose in numerous cell types. In such cases, energy would be preferentially shunted to the tumour, and away from normal cells by cortisol (Romero et al, 1992). Thus, there are a variety of means by which depression-related abnormalities in HPA function could affect the rate of cancer progression.…”
Section: Hpa Dysregulation and Cancer Progressionmentioning
confidence: 99%
“…Tumour cells become resistant to the catabolic action of cortisol, which inhibits the uptake of glucose in numerous cell types. In such cases, energy would be preferentially shunted to the tumour, and away from normal cells by cortisol (Romero et al, 1992). Thus, there are a variety of means by which depression-related abnormalities in HPA function could affect the rate of cancer progression.…”
Section: Hpa Dysregulation and Cancer Progressionmentioning
confidence: 99%
“…These authors concluded that this inhibition was caused by decreased rates of glucose transport and protein synthesis in the cells, which are well established effects of glucocorticoids on fibroblasts. In another study that included microphysiometry, this group discovered that virally transformed fibroblasts were resistant to such metabolic inhibition (60). The authors proposed that stress, which causes the secretion of glucocorticoids, accelerates the growth of some types of tumors by this mechanism.…”
Section: Applications Of Microphysiometrymentioning
confidence: 98%
“…Glucocorticoids have been implicated in tumor growth, both in animal and in in vitro studies [26,27]. Cortisol may accelerate tumor growth via immunosuppressive actions or effects on metabolic processes [28,29]. When cortisol profiles are affected, dysregulated patterns of immune activity and immune cell trafficking may also emerge [30].…”
Section: Discussionmentioning
confidence: 99%